Submergence and uplift associated with the giant 1833 Sumatran subduction earthquake : evidence from coral microatolls - Taylor, Frederick W. (2012)
The giant Sumatran subduction earthquake of 1833 appears as a large emergence event in fossil coral microatolls on the reefs of Sumatra's outer-arc ridge. Stratigraphic analysis of these and living microatolls nearby allow us to estimate that 1833 emergence increased trenchward from about 1 to 2 m. This pattern and magnitude of uplift are consistent with about 13 m of slip on the subduction interface and suggest a magnitude (Mw ) of 8.8–9.2 for the earthquake. The fossil microatolls also record rapid submergence in the decades prior to the earthquake, with rates increasing trenchward from 5 to 11 mm/yr. Living microatolls show similar rates and a similar pattern. The fossil microatolls also record at least two less extensive emergence events in the decades prior to 1833. These observations show that coral microatolls can be useful paleoseismic and paleogeodetic instruments in convergent tectonic environments.